Enhancing mathematical statistics learning: Development of a LaTeX-based module - Arifin, M. Zainul (Indonesian Journal of Science and Mathematics Education, 2026)
Learning mathematical statistics requires students to interpret abstract concepts, symbolic notation, and multi-step statistical procedures. This study developed a LaTeX-based instructional module for the Introduction to Mathematical Statistics course and examined its validity and readability. The study used an Research and Development approach based on a modified 4D model, limited to the Define, Design, and Develop phases. Data were collected from one expert validator and 27 students through a validation sheet, a readability questionnaire, and open-ended feedback. Quantitative data were analyzed using descriptive statistics, while qualitative comments guided revisions. The expert-validation score was 3.68, placing the module in the highly valid category; the language aspect received the highest score (4.00). The student readability score was 4.60 on a five-point scale, categorized as very good, with text clarity receiving the highest score (4.85). Grammar and worked-example steps were relatively lower but still positive. The findings indicate that LaTeX supports consistent notation, equation alignment, and more readable mathematical representations when combined with clear explanations and structured examples.